A Monte Carlo based simulation method for damage stability problems - Krüger, Stefan; Dankowski, Hendrik (Volume 3: Structures, Safety, and Reliability, 2019)
To cope with future developments of the SOLAS 2009 B1, damage stability investigations must become a central part of the initial design phase. If damage stability calculations are performed in the classical way, they are very time consuming with respect to both modelling and computational time. To overcome this problem, damage stability can be treated as a stochastic process, where the probability of a damage case and the survivability of that particular damage case need to be determined. This task can be solved by direct numerical simulations based on the Monte Carlo principle. If statistical damage distributions are once known, the Monte Carlo simulation delivers a population of damages which can be automatically related to certain damage cases. These damage cases can then be investigated with respect to their survivability. Applying this principle to SOLAS 2009 damage stability calculations leads to a number of implementation problems which must be solved to guarantee that the MC simulation delivers exactly the same results as the manual, zone based damaged stability calculation. If these problems are solved, the MC based damage stability calculations can be used during the initial design phase until the damage stability approval. The proposed method reduces the computational effort drastically which supports the initial design phase of the ship's compartmentation. The method further leads to higher attained indices and consequently to a safer and more efficient design.